The shining [videorecording (DVD)] - Kubrick, Stanley; Harlan, Jan; Nicholson, Jack; Duvall, Shelley, 1949-2024; Lloyd, Danny, 1973-; King, Stephen, 1947- (Stanley Kubrick collection., 2010)
When a couple takes a job as hotel caretakers for the winter, their young son's psychic powers bring out the evil in the old hotel.